Bosnia and Herzegovina : Capital Markets Technical Note - World Bank; International Monetary Fund (World Bank, Washington, DC, 2015)
This Technical Note was prepared in the context of a joint World Bank-IMF Financial Sector Assessment Program mission in Bosnia and Herzegovina during October-November 2014. Bosnia’s capital markets are currently small, but they have the potential to play a more important role in the country’s future.